Pengaruh Kebijakan Dividen, Kebijakan Hutang, dan Profitabilitas terhadap Nilai Perusahaan pada Perusahaan Manufaktur yang Terdaftar di Bursa Efek Indonesia - Angela Komala; Budi Kurniawan (KALBISIANA Jurnal Sains, Bisnis dan Teknologi, 2022)
This study aims to show and provide information on how a company can be measured by three important aspects of the company, namely dividend policy, debt policy, and profitability. The testing method in this study uses multiple linear analysis. With a pandemic like this, some companies, especially in certain sectors, will definitely experience a decline in profits. However, many companies have also changed their policies so that companies can survive in the midst of a pandemic. The research sector in this study is the ceramic, glass, and porcelain sector using their financial statements for the period 2016 – 2020. The results of this study state that in the ceramic, glass and porcelain sector, dividends and debt policy do not affect firm value. but profitability that affects the value of the company. The researcher hopes that this research can be useful for investors, the general public, and also in the future.